Kontribusi Teknologi Informasi dan Komunikasi terhadap Rata-Rata Lama Sekolah di Pulau Jawa - Dyah Makutaning Dewi; Andaro Fransiando Saingan; Yusriza Fahmi (Universitas Negeri Padang, 2022)
Education is one of the capital in building human resources. Through education, people can add knowledge and skills that will be used in the future or the present. The number of facilities offered in Java Island, many young people who prefer to study in the region compared to the outer region of Java Island. The use of Technology, Information, and Communication (ICT) in the field of education has a large role in the learning process. The purpose of this study is to describe the Mean Years of Schooling and ICT and analyze the influence of ICT on the increase in average length of school in Java Island. The data used is sourced from data from the Statistics Indonesia-BPS in the period 2017 until 2020. The results showed the Mean Years of Schooling, internet users, and computer users tended to increase in Java. The variables of internet users, computer users, and capital expenditures have a positive and significant influence on the Mean Years of Schooling in Java while the percentage of poverty does not have a significant influence. Therefore, collaboration between various parties is needed in improving ICT support infrastructure. The government should be able to allocate funds for education appropriately. In addition, the school should register students who have difficulty in accessing the internet.